Evaluation of the relationship between pain inflammation due to dental caries and growth parameters in preschool children. - Gunay, Basak; Kaya, Mustafa Sarp; Ozgen, Ilker Tolga; Guler, Eray Metin; Kocyigit, Abdurrahim (My University, 2023)
To evaluate the relationship between pain inflammation due to dental caries and growth parameters, sleep disturbances, and oral health-related quality of life (OHRQoL) in preschool children before/after dental treatment and compare the results with the control group.

Study (pain inflammation due to caries) and control groups were included in this prospective clinical trial. The Child Sleep Habits Questionnaire (CSHQ) assessing sleep disturbances and the Early Childhood Oral Health Impact Scale (ECOHIS) assessing OHRQoL were applied in the corresponding time intervals to the study and control groups, respectively: baseline (T0), 7 days after treatment (T1), and following 6 months (T2); baseline (T0), and the following 6 months (T2). Biochemical growth parameters (insulin-like growth factor-1 and insulin-like growth factor binding protein-3) and anthropometric measurements (standard deviation score of height, weight, and body mass index) were obtained at T0, T2, and T0. Mann-Whitney U and the Student t-tests were used for statistical analyses. The significance level was set at p < 0.05.

Data on 45 children (mean age: 55.6 ± 10.37 months) were analyzed. T2 was statistically higher than T0 for the anthropometric measurements and biochemical growth parameters (p < 0.05). T0 was statistically higher than T0 for biochemical growth parameters (p < 0.05). CSHQ and ECOHIS scores were found statistically significant at T0 than T0 (p < 0.05). Statistical scores of CSHQ and ECOHIS in T2 were significantly reduced compared to T0 (p < 0.05).

Children's growth parameters, sleep disturbances, and OHRQoL improved after the elimination of pain and inflammation.

This study's novelty is the observation of drastically increased growth parameters and reduced sleep disturbances following dental treatment.
Keywords: Child; Dental caries; ECOHIS; Growth; Sleep disturbances